Pharmacologic Treatment of Meningitis and Encephalitis in Adult Patients - Treister, Andrew K.; Koerner, Ines P. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Meningitis and encephalitis are two inflammatory, often infectious, disorders of the meninges and the central nervous system. Both are associated with significant morbidity and mortality, and require early and aggressive targeted treatment. This article reviews pharmacologic treatment strategies for infectious meningitis and encephalitis, using the latest available research and guidelines. It provides an overview of empiric antimicrobial treatment approaches for a variety of organisms, including a discussion of trends in antibiotic resistance where applicable. Key steps in diagnosis and general management are briefly reviewed.
Keywords: meningitis; encephalitis; antibiotic resistance